Effect of inoculation of Bacillus megaterium isolates on growth, biomass and nutrient content of Peppermint - C, Sandeep; Venkat Raman, R; M, Radhika; S, Thejas M; Patra, Sanjeev; Gowda, Tejaswini; K, Suresh C; Mulla, S R (Journal of Phytology, 2011)
The investigation was carried out to study the effect of Bacillus megaterium isolates on growth, biomass and nutrient content of Pepper mint. Pepper mint was used as a host plant to study the growth response, biomass and nutrient content. Bacillus megaterium strains from different soil types of various agroclimatic zones were isolated, identified and confirmed using standard synaptic keys. A pot culture experiment was carried out to find out the influence of Bacillus megaterium isolates on seedlings of Pepper mint under greenhouse conditions. Pepper mint plants inoculated with Bacillus megaterium isolates manifested increase in plant height, number of leaves, number of branches, biomass and nutrient content compared to uninoculated plants. Among the ten isolates inoculated, the Bacillus megaterium isolates from zone 3 showed significantly high values in almost all growth parameters chosen for the study. Similarly biochemical parameters of the Pepper mint inoculated with ten isolates of Bacillus megaterium was studied. In the inoculated plants the biochemical parameters like chlorophyll content, nitrogen content and phosphorus content was higher as compared to uninoculated plants. The results suggests that plants inoculated with Bacillus megaterium isolates showed better growth response, biomass yield and nutrient content when compared to uninoculated plants. Also the studies showed that Zone 3 isolate was more effective among other isolates.